1983
DOI: 10.1111/j.1365-2265.1983.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Gonadal Suppression in Fertile Women With the LHRH Agonist Buserelin

Abstract: Nine fertile women were treated with the luteinizing- hormone-releasing hormone agonist buserelin (seven women received 800 micrograms, two women 1200 micrograms intranasally for up to 24 weeks). Both doses produced sustained suppression of ovarian function, accompanied by hot flushes. In five women chemical castration was established within 1 to 5 weeks, whereas in the other four volunteers transient peaks of serum oestradiol occurred between the 6th and 19th weeks. Thereafter low postmenopausal oestradiol le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 5 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Ovulation either did not occur (Hardt & Schmidt-Gollwitzer 1983;Kuhl et al 1984) or was rare occurring in 3 of 628 treatment cycles and attributed to early technical problems with the nasal spray application (Bergquist. et al 1984).…”
Section: Ovulation and Pregnancy Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Ovulation either did not occur (Hardt & Schmidt-Gollwitzer 1983;Kuhl et al 1984) or was rare occurring in 3 of 628 treatment cycles and attributed to early technical problems with the nasal spray application (Bergquist. et al 1984).…”
Section: Ovulation and Pregnancy Ratementioning
confidence: 99%
“…Note that the efficacy of intranasal LHRH agonist contraception is dose-related. Amenorrhoea occurred in 25% of women on therapy, more particularly on higher doses (Hardt & Schmidt-Gollwitzer 1983). By contrast, doses of 100 yg LHRH agonist daily intranasally allowed 31 of 48 cycles to be ovulatory and one subject conceived (Schmidt-Gollwitzer et a/.…”
Section: Ovulation and Pregnancy Ratementioning
confidence: 99%
“…Meldrum et al (1982) have reported the first successful treatment with daily administration of a 100-^g dose of a GnRH agonist, oestrogen and androgen levels being reduced to castration levels in one month. After the cessation of a sustained gonadal suppression with the agonist (buserelin), normal cyclical function in fertile women occurred immediately (Hardt and Schmidt-Gollwitzer, 1983). The treatment was well tolerated in spite of the expected hot flushes and vaginal dryness (Lemay et al, 1984).…”
Section: Endometriosismentioning
confidence: 97%
“…18 Buserelin was chosen from among other synthetic LHRH-As because of its potent and specific LHRH activity and its strong ability to cause a reversible medical castration. 15 Luteinizing hormone releasing hormone is a hypothalamic decapeptide which is carried through the pituitary portal system from the eminentia mediana to the anterior pituitary gland. It binds specifically to high affinity receptors on the pituitary gonadotrophic cells and stimulates the synthesis and release of gonadotrophins (LH and FSH).…”
Section: Casementioning
confidence: 99%